Case Report: Implementation of stereoelectroencephalography in Kazakhstan: early experience in surgical planning for drug-resistant epilepsy - Abzalova, Veronika; Kauynbekova, Sholpan; Makhambayev, Gabit; Dmitriev, Aleksandr; Tuleubayev, Berik (Frontiers in Human Neuroscience, 2025)
IntroductionThis clinical report describes the management of a 32-year-old patient with a long-standing history of drug-resistant epilepsy. It uniquely illustrates how stereoelectroencephalography (SEEG) played a significant role in the presurgical evaluation of a multifocal epileptic disorder which, despite a long history of no changes on MRI, was ultimately found to be associated with bilateral hippocampal sclerosis. This is one of the first documented cases of SEEG application in Kazakhstan, where the method was introduced in 2024.Clinical presentation and diagnostic findingsThe patient suffered from debilitating seizures (4–6 times/week, often in series of 3-4/day) refractory to combined antiepileptic therapy. Scalp EEG revealed the first originating from the right frontotemporal leads with subsequent diffuse, predominantly right-sided, propagation. The second seizure, however, showed onset from the left temporal leads; notably, only left-onset seizures culminated in bilateral synchronization. Financial constraints precluding PET-CT and the diagnostic ambiguity of routine methods necessitated invasive SEEG.SEEG results and therapeutic strategySEEG monitoring unequivocally identified three independent epileptogenic foci: in the right hippocampus, left hippocampus, and left orbitofrontal region. Such multifocal pathology significantly reduces the likelihood of successful focal resection. Despite this inherent complexity, a crucial clinical outcome was achieved: the patient has remained completely seizure-free for 7 months following the ANT-DBS procedure.ConclusionThis report underscores the critical role of SEEG in the precise localization and characterization of complex, multifocal epileptogenic networks, often elusive to non-invasive modalities. It convincingly demonstrates that a comprehensive invasive approach can lead to successful seizure control even in cases previously considered inoperable. It also reflects the challenges and advancements in developing high-tech epileptological care in regions where advanced methods like SEEG have only recently been introduced.